Ethnography, Applied Theatre and Stiwanism: Creative Methods in Search of Praxis Amongst Men and Women in Jinja, Uganda. (22nd June 2017) - McQuaid, Katie; Plastow, Jane
Abstract: This article critically reflects on a long‐term intergenerational project combining ethnographic and social science research methods and Freirean‐inspired applied theatre in a long‐term participatory process working alongside men and women in search of a 'plenitude of praxis': strengthening and promoting an urban community's capacity to unite across social barriers in recognising systemic injustices and inequalities and challenging these through community‐led interventions in pursuit of common social justice outcomes. It reflects on the successes, complexities and failures of an approach rooted in African feminism, and in particular stiwanism, in a context of entrenched urban poverty in Jinja Municipality, Uganda. Copyright © 2017 John Wiley & Sons, Ltd.